Optimal Product Pricing and Recovery Strategies in a Two-period Model for Manufacturers with Core Classification and Trade-In-for-New/Reman Policies - Wang, Zhe; Cao, Peipei; Xu, Fan (Asia Pacific Economic and Management Review, 2025)
Motivated by the recent policy initiative of the Central Financial and Economic Affairs Commission to promote a new round of equipment upgrading and consumer-goods trade-in programs, we develop a two-period game-theoretic model for a manufacturer endowed with remanufacturing capability. In period 1, the market is partitioned into new and remanufactured products, and the initial market structure is determined by their respective demand shares. In period 2, consumers’ trade-in/-for-remanufacturing behavior is disentangled; utility theory is employed to derive demand functions under alternative scenarios. The manufacturer then chooses the sales prices of both new and remanufactured products together with the buy-back price of used new products so as to maximize its total profit. Key findings are as follows. (1) The new-product demand share, the trade-in discount for remanufactured items, and the product’s circular value are the three pivotal drivers of pricing strategy. In particular, when the new-product demand share is low, the circular value is high, or the remanufactured-product trade-in discount is large, the optimal buy-back price of new products equals the selling price of remanufactured products. (2) The sales prices of new/remanufactured products and the buy-back price increase with the remanufacturing trade-in discount and consumers’ perceived-value discount, decrease with the circular value, and rise with the new-product production cost. (3) The impact of the new product’s circular value on pricing depends on the market structure: only when the new-product demand share is high, the trade-in discount is low, and the circular value itself is small will an increase in circular value raise all prices. (4) Under a high remanufactured-product pricing strategy, the buy-back price is U-shaped in the new-product demand share; under a low pricing strategy it increases monotonically. (5) Manufacturer profit increases with the remanufacturing trade-in discount, the circular value, and the perceived-value discount, but decreases with the remanufacturing circular value. A lower new-product demand share and higher production cost reduce total profit; however, once the cost exceeds a critical threshold, profit rebounds. We recommend that manufacturers dynamically adjust pricing, invest in remanufacturing technology, and enhance recovery incentives. Meanwhile, governments should underpin green consumption and the circular economy through supportive policies and effective oversight.